Tingkat Pengetahuan Masyarakat Tentang Dagusibu Obat (Dapatkan, Gunakan, Simpan Dan Buang) Di Desa Kedung Bendo Kelurahan Tambakboyo Kota Ngawi - Andini, Amin Suryaandini (Universitas Kadiri, 2023)
Dagusibu Drug (Get, Use, Save and Waste ) is a survey program in realizing the level of public knowledge in the Drug Awareness Family Movement (GKSO). The purpose of this research is to increase public knowledge about Dagusibu Obat. This type of research is a quantitative descriptive type with a survey or questionnaire method. The sample in this study were the people of Kedung Bendo Village Rt 01, 02, 03 Rw 09 Tambakboyo Village, Ngawi City with a total of 96 respondents. The results of the study were obtained from 96 respondents regarding knowledge about Dagusibu about getting medicine with a very understanding percentage (85%) and (65%) in the understanding category, using drugs with a very understanding percentage (87%), 65% in the understanding category, ( 40%) in the category of not understanding and 26.6% in the category of not really understanding. Save drugs with a percentage (73.5%) in the category of very understanding, (63.5%) in the category of understanding, (45%) in the category of not understanding and 26.5% in the category of not really understanding. Dispose of drugs with a percentage (30%) falling into the category of not understanding and (23%) falling into the category of very uncomprehending.